Derivaciones urinarias del tracto urinario superior en el anciano. - Corral Rosillo, J.; Esteban Fuertes, M.; Hermida Gutiérrez, J.; Luengo Alpuente, S.; Mohamed Mohamed-abdallah, Z.; Moreno Sierra, Jesús; Ramírez Fernández, J.C.; Resel, Luis; Silmi Moyano, A.; Blanco Jiménez, E. (Clínicas Urológicas de la Complutense, 1993)
Sin resumen